KINERJA SISTEM JARINGAN DRAINASE KOTA SEMARAPURA DI KABUPATEN KLUNGKUNG - Suryanti, Irma; Norken, I N.; Sila Dharma, I G. B. (JURNAL SPEKTRAN; Vol 1, No 1, Januari 2013, 2013)
Urban drainage is one of basic facilities and infrastructure of a town which is cincidered quite important. Agood city needs to consider the condition of the drainage system, because if a settlement is flooded, it will greatly impact the lives of the city. Buildings will be easily damage, environments will be unhealthy and settlements will turn into slumps. The case of flooding is not only in big cities but also emerged in the town of Semarapura that extents only, 5,151 km2. From the conditions on ground, puddles can still be found in some locations, so based on the fact it is necessary to issue reviewing Semarapura drainage system to improve the drainage system in the region. The study in this research has the sense of a systematic search of the drainage problems from an investigation in order to get treatment effort. The approach applied in this research was exploratory and descriptive analytical approach. Data were collected through questionnaires an in-depth interviewers with selected agencies using purposive sampling method. Data analysis was perfomed by descriptive qualitative using likert scale to measure the attidudes, opinions and perceptions of tge performance of the drainage system. The analysis was performed with the aids of SPSS version 20.0, through several stage of the test process to the data sample. The result of the study showed that the influence of the level of maintenance operation, technical management and overall was high at 93,5% with the regression equation Y = -4.874 + 0.405 X1 + 0.228 X2 + 0.089 X3 and the remaining 6.5% was influenced by other factors. From the equation it can be seen that the maintenance operations were more dominantly affected on the performance of the drainage system in Semarapura town District of klungkung compared with management and technical. The effort carried out to increase performance system of Semarapura town drainage network is to construct a structured system of maintenance operations so that it can be performed on a regular basic, establish drainage management institutions that it’s authority and responsibility can be coordinated as directed an make clear rules of management system, make repairs damage drainage infrastructure in accordance with the technical requirement.
Keywords: operation and maintenance, drainage system performance